Fetal and neonatal alloimmune thrombocytopenia – The Norwegian management model. (February 2020) - Tiller, Heidi; Ahlen, Maria Therese; Akkök, Çiğdem Akalın; Husebekk, Anne
Highlights: The antenatal management of HPA-1a alloimmunization in Norway is different from most other countries. Antenatal IVIg is only recommended if a mother has previously had a neonate with intracranial haemorrhage caused by FNAIT. Abstract: In Norway, the management strategy for fetal and neonatal alloimmune thrombocytopenia (FNAIT) has for more than two decades differed from most other countries. The focus of this paper is to describe and discuss the Norwegian FNAIT management program. We recommend antenatal IVIg to women who previously have had a child with FNAIT-induced ICH, and usually not to HPA-1a alloimmunized pregnant women where a previous child had FNAIT, but not ICH. When deciding management strategy, we use not only the obstetric history but also the antenatal anti-HPA-1a antibody level as a tool for risk stratification. The Norwegian National Unit for Platelet Immunology (NNUPI) at the University Hospital of North Norway in Tromsø provides diagnostic and consulting service for the clinicians and the blood banks all over the country, and serves as a national reference laboratory for FNAIT investigations.